(untitled) (Neo Science Peer Reviewed Journal, 2023)
Hippocampal sclerosis (HS) is the most common (60-85%) pathological substrate in patients with refractory temporal lobe epilepsy and is encountered in 65% of adult temporal lobectomy specimens. Although its pathophysiology is not completely understood, neuronal loss and accompanying astrogliosis of the hip- pocampal formation constitute the main histopathological features of HS. The CA1 sector principally and secondly the CA3 sector and the hilus of the dentate gyrus are the most severely affected parts of the hippocampal formation.